HUMAN RESOURCE COMPETENCIES FOR MANAGING CHALLENGES - Mangaleswaran, T.; Srinivasan, P.T. (Mangalore University, 2006)
Worldwide, all organizations arc facing lot of challenges, which influence the organization’s performance, survival and existence. Organization spends most of their time to learn it and thinking how to overcome or manage those challenges. They have understood the importance of the development of Human Resource Competencies as one of the cool to overcome human resource challenges. The success of human resource professional`s performance depend on the Human Resource Competencies which they posses. Therefore it is essential to every Human Resource Professionals to develop themselves to be effective manager. This paper offers answers to the questions such as what is the meaning of Human Resource Competencies. And what competencies human resource managers need to succeed or develop? What is the meaning of Human Resource challenges? What are the Human Resource challenges? Are the major challenges encounters by the Human Resource competencies?